Effect of triazole - triadimefon on tolerance to moisture stress in wheat (Triticum aestivum) ABSTRACT - Sairam, R K; Shukla, D S; Deshmukh, P S (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during winter season of 1989-90 and 1990-91 to study the effect of triadimefon on moisture stress in ’C 306" ’HD 2428’ and ’HD 2329’ genotypes of wheat (Triticum aestivum L. emend, Fiori & Paol.). Moisture stress decreased the relative water content (26%), transpiration (82%), chlorophyll (29%) and protein (27%). Triadimefon further reduced the transpiration and increased the relative water content and membrane stability under both the conditions. The effect of triadimefon was more in droughtÂ·tolerant genotypes ’C 306’ than the susceptible’ HD 2428’. Significant incrcase was also observed in chlorophyll content (24%) and protein content (56%) in triadimefonÂ·treated plants. There was increase in tillers/plant, green leaves/plant and leaf area/plant, though the individual leaf size was slightly reduced by triadimefon application. Triadimefon 1 000 ppm significantly increased the yield (13%), grains/ear (10.5%), 1000-grain weight (8%) and harvest index (13%). The stimulatory effect was more in drought tolerant genotype than in suspectible one in post as well as in field under moisture stress.